Predictor of early post-operative small bowel obstruction in patients undergoing emergency laparotomy and the role of computed tomography in detecting need for re-laparotomy - Singh, Sunil Kumar; Singh, Arun; Kumar, Rajnikant (International Surgery Journal, 2018)
Background: Early Post-Operative Small Bowel Obstruction (EP-SBO) is common complication following laparotomy. Pathophysiology of early post-operative small bowel obstruction is poorly understood. Methods: This cross-sectional observational study was conducted over a period of 18 month on 180 patients who underwent emergency abdominal laparotomy. Results: EP-SBO developed in 35.55% patients. History of previous surgery, location of disease, degree of peritonitis, operative procedure, wound dehiscence was found to be significantly related with occurrence of EP-SBO. Conclusions: EP-SBO is more likely to develop if patient had history of previous surgery, peritonitis, some operative procedure, ostomy, wound dehiscence. We should have a preventive attitude towards any risk factor at any stage- Before, During and After surgery and CECT-Abdomen is a helpful tool in establishing need of re-laparotomy.